Community Engagement in Southeast Asia’s Tourism Industry: Empowering Local Economies - Rahman, Shati Sarmin; Baddam, Parikshith Reddy (Global Disclosure of Economics and Business, 2021)
Community engagement is increasingly recognized as a crucial component of sustainable tourism development in Southeast Asia. This study examines the role of community engagement in empowering local economies within the region’s tourism industry. The main objectives were to analyze current community engagement practices, assess their impacts on regional economies, and identify challenges and opportunities for sustainable development. A secondary data-based review approach was employed, drawing from academic journals, reports, and government publications. Significant findings reveal that community-based tourism initiatives drive economic empowerment and foster cultural preservation and social cohesion. However, challenges such as power imbalances and environmental degradation persist. Policy implications underscore the need to strengthen community engagement mechanisms, promote sustainable tourism practices, support local entrepreneurship, and foster partnerships and alliances among stakeholders. By addressing these challenges and implementing appropriate policies, Southeast Asia can create more inclusive, resilient, and sustainable tourism destinations that benefit communities and visitors.